Unsteady MHD flow of viscous and second grade fluids in a porous medium - Zulkhibri, Ismail @ Mustofa (2016)
In this thesis, the unsteady magnetohydrodynamic (MilD) free convection flows of viscous and second grade fluids past an infinite inclined plate in a porous medium are studied. These viscous and second grade fluids are under the conditions of ramped wall temperature and isothermal plate. Analytic solutions are developed by using Laplace transform technique. The main finding of this thesis is to determine the expressions of exact solutions for velocity, temperature and concentration profiles. All these profiles are graphically plotted for various physical parameters such as radiation, heat absorption, porosity, rotation and second grade parameters. The results show that when temperature decreases, high radiation and heat absorption occurs which consequently decreases the velocity. For larger values of magnetic parameter, the fluid velocity decreases. The velocity is found to increase with increasing values of the porosity parameter. It is also observed that when the second grade parameter increases, the velocity shows an oscillating behavior where the velocity first decreases and then increases. An interesting result for the velocity is observed from the comparison of ramped wall temperature and isothermal. It is found that fluid velocity retarded in the case of ramped wall temperature compared to isothermal case. In limiting cases, the present solutions are reduced in order to compare with existing results. As expected, the results are found identical, verifying the validity of the obtainable solutions. The numerical results of skin-friction, Nusselt number and Sherwood number are also computed and displayed in tables, and also analyzed in details.